Innovative mineral carbonation techniques: A comprehensive review of ultrasound-assisted processing, mechanistic insights, optimization strategies, and environmental impacts - Xun Sun; Haozhen Xu; Sivakumar Manickam; Rakesh Kumar Gupta; Giancarlo Cravotto; Joon Yong Yoon; Benlong Wang; Wenlong Wang; Di Sun (Carbon Capture Science & Technology)
Worldwide efforts are focused on reducing CO2 emissions and improving CO2 capture, utilization, and sequestration. Ultrasound-assisted processing (UAP), utilizing acoustic cavitation (AC), emerges as a promising, eco-friendly technology to enhance CO2 sequestration. This overview highlights recent progress in UAP for mineral carbonation, covering intensification mechanisms, sonochemical reactors, and the impact of UAP factors (frequency, power, temperature, particle size, duration, pH). High temperatures (5000 K) and pressures (1000 atm) from AC generate hydroxyl radicals, boosting mass transfer and reaction rates while preventing passivating layer formation. These factors accelerate CO2 sequestration. UAP can increase carbonation/leaching rates by 10–40% with lower energy consumption and milder conditions than conventional methods like high-temperature reactors. However, further research is needed to improve economic efficiency and scalability, as key challenges include controlling acoustic field uniformity, ensuring consistent performance across varying mineral types, and integrating UAP with existing industrial infrastructure.